Fotocatálise do antibiótico sulfametoxazol utilizando nitreto de carbono grafítico e quitosana, com avaliação toxicológica - Christan, Rhaissa Dayane Carneiro de (2023)
The inefficiency of removing emerging contaminants through conventional methods of effluent treatment contributes to the frequent detection of the antibiotic sulfamethoxazole and its metabolites in receiving water bodies. Therefore, it is necessary to study and develop new technologies to remove this contaminant. In this context, the use of heterogeneous photocatalysis appears as an alternative. The polymeric catalyst, graphitic carbon nitride, attracts attention because it is a metalfree material, absorbs visible light (~455nm) and is low cost. The objective of this work was to evaluate the degradation and toxicity of the antibiotic sulfamethoxazole, before and after photocatalysis using graphitic carbon nitride (in powder form) and chitosan microspheres with urea. In the degradation tests to evaluate the photocatalytic activity of the materials, the removal of the antibiotic Sulfamethoxazole was evaluated, comparing it with photolysis. Different sources of radiation were also used in the photocatalysis, in order to compare; with the UVA-Vis source, a high pressure mercury vapor lamp was used, with a power of 125 W and the degradations were also compared using the lamp suspended (S) at 10 cm from the solution and dipped in solution (M); with a visible radiation source, a Halogen lamp (brand Xelux, 250 W) and also an LED lamp (brand ASUS, 40 W) were used, both suspended at a distance of 10 cm from the reactor. Through the technique of high performance liquid chromatography (HPLC-FLD) the efficiency of the degradations was verified. Using UVA-Vis radiation (M), with graphitic carbon nitride (powder), the efficiency was 96.93%; already with the microspheres it was 99.71% and by photolysis it was 100%. UVA-Vis (S), with graphitic carbon nitride (powder), the efficiency was 66.34%; already with the microspheres it was 37.29% and by photolysis it was 56.96%. With halogen lamp and graphitic carbon nitride (powder) the efficiency was 17.40%; with the microspheres, the degradation of the antibiotic could not be observed, and by photolysis it was 29.17%. With LED lamp and graphitic carbon nitride (powder) the efficiency was 33.69%; with the microspheres and by photolysis, the degradation of the antibiotic could not be observed. Before and after degradation, toxicological monitoring was carried out to determine acute toxicity to Daphnia magna and phytotoxicity with Lactuca sativa seeds. In all processes, by-products were produced with varying levels of toxicity over the course of degradation. However, it was possible to observe that in the photodegradation using the material graphitic carbon nitride (in powder), with all the lamps, there was a decrease in toxicity over the treatment time, in comparison with the photodegradations using the chitosan microspheres with urea. Relating the results of the toxicological monitoring with the efficiency of the proposed treatments, it was possible to establish that the photocatalysis using a UVA-Vis lamp (M) with graphitic carbon nitride (in powder) was the most effective method in the treatment for the degradation of the antibiotic sulfamethoxazole.